BREAKING THE CARBON ACCOUNTING LITERACY GAP THROUGH VOCATIONAL TEACHERS AS A SYSTEMIC LEVERAGE POINT IN THE GREEN ECONOMY TRANSITION - Lin Oktris; Afzal Izzaz Zahari; Suharmadi; Hirdinis M.; Rafli Adhira Saputra; Metta Ciptaningtyas; Widya Simamora (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
The global transition toward a green economy fundamentally transformed the landscape of the accounting profession, yet this transformation had not fully reached the vocational education system responsible for producing Indonesia's accounting workforce. This study showed that the carbon accounting literacy gap among vocational accounting teachers was not merely a matter of individual competency, but reflected a systemic failure that created a chain of ignorance from educators to students to the workers entering the labor market. Using a qualitative approach based on participatory observation of a training program involving 50 vocational accounting teachers from the Tangerang Accounting Teacher Association at Universitas Mercu Buana in April 2026, this study found that nearly all participants had never been exposed to carbon accounting concepts or greenwashing identification frameworks in any prior formal professional training. This finding confirmed that the existing gap was systemic rather than individual in nature. This study further showed that vocational teachers represented the most efficient leverage point for breaking this chain of ignorance, as the multiplier effect inherent to the teaching profession allowed a single training intervention to impact thousands of future workers. The implications of these findings pointed to the need for systemic reform in the professional development of vocational accounting teachers as a prerequisite, rather than a consequence, of Indonesia's successful green economy transition.